Asymptotic formula for the Riesz means of the spectral functions of Laplace-Beltrami operator on unit sphere - Nurullah Rasedee A.F.; Ahmedov A.; Abdul Sathar M.H. (Institute of Physics Publishing, 2024)
Indexed by SCOPUS